A new species of the infaunal alpheid shrimp genus Richalpheus Anker & Jeng, 2006 (Decapoda: Caridea) from Kagoshima, Japan - Komai, Tomoyuki; Koreeda, Reo (Zootaxa, 2022)
A new species of the alpheid shrimp genus Richalpheus Anker & Jeng, 2006 is described on the basis of 10 specimens collected from three locations in Kagoshima Prefecture, Kyushu, Japan. Richalpheus laeuadigitus n. sp. appears close to R. palmeri Anker & Jeng, 2006 and R. dahabensis Anker & Dworschak, 2007 among the three known congeners, but differs from R. palmeri in the proportionally wider telson and the more proximally located tip of the antennular stylocerite, and from R. dahabensis in the different configuration of the major cheliped fingers, in particular the possession of a well-developed bulge-like ridge on the occlusal margin of the dactylus. Two sequences of the mitochondrial 16S rRNA gene from two of the paratypes are newly obtained, and compared with that of R. palmeri downloaded from the GenBank database. The new species is the fourth representative of Richalpheus. Possible association between the new species and other infaunal invertebrates is suggested, although not specified.